The microbiological quality of some critical control points in the cheese production of individual Slovenian cheese-makers - Karmen GODIČ TORKAR; Slavica GOLC TEGER (Acta Agriculturae Slovenica)
The microbiological quality of 98 samples taken at some critical control points during the milking and processing of 14 semi-hard cheese made from raw cow milk by individual Slovenian producers was studied. The sampling points were: swabs from cows’ udders, milking machines inner surfaces before and after milking, fresh raw and mixed milk from vats, whey immediately after curdling, brine, cheese after one month of ripening and after the following month of being kept vacuum packed at 6 °C. The high number of micro-organisms on the inner surfaces of washed milking machines before milking revealed ineffective cleaning (washing) by about 60% of cheese producers. There were no seasonal differences in the number of micro-organisms, except that the number of coliforms was higher in spring. The average of total number of micro-organisms was 4.9·105 cfu/ml in raw milk and 5.5·106 cfu/ml in mixed milk from a vat (raw fresh milk mixed with milk kept for about 18–24 hours at room temperature), which did not grow significantly during cheese-processing. The number of coliforms in raw and mixed milk was in the range of 3.4·105 cfu/ml and fell to 5.4·104 cfu/ml in whey. The average number of enterococci, aerobic spore-forming micro-organisms, yeasts and moulds, lactobacilli, lactococci, proteolytic and lipolytic micro-organisms in milk and in whey were in the same logarithmic range of about 2.2·104, 310, 3.5, 31.2·104, 2.1·106, 6.2·103 and 1.7·104 cfu/ml of the sample, respectively. Listeria spp. was isolated from 5.3% (cows’ udders, milking machine, milk and whey), while none of the examined samples were positive to the presence of Salmonella spp. and Campylobacter spp. Proteus was present in 7 (7%) cases of milk and whey. Clostridia were detected in 10 (10%) samples (swabs, raw milk, whey). E. coli was isolated from 12 (12%) samples of swabs, raw and mixed milk, whey and brine. After one month of ripening the average total bacterial count was 9.2·107 cfu g–1 of cheese, of these 6.8·107 represented lactic-acid producers and 2.2·107 represented non-lactic acid producers. The average number of coliforms, enterococci, aerobic spore-forming micro-organisms, yeasts and moulds, lactococci, lactobacilli, proteolytic and lipolytic micro-organisms were 2.0·105, 6.3·106, 280, 960, 2.5·107, 9.8·107, 450 and 9.8·104 cfu g–1 of cheese, respectively. Salmonella spp., Listeria spp., Proteus, sulphite-reducing clostridia and Campylobacter spp. were not detected in cheese samples. E. coli was found in 4 (30%) of samples while coagulase positive staphylococci were present in 9 (64%) of cheese samples. A high number of enterococci (from a min. 3.103 to a max. 15.107 cfu g–1) and coliforms (from a min. 10 to a max. 19.105 cfu g–1) were detected as well. After one month of keeping vacuum-packed ripened cheeses at 6 °C, the number of micro-organisms did not rise significantly, except for the number of yeasts and moulds which grew to 3.6·104 cfu g–1 of cheese. Because of improper milking and processing hygiene conditions, three (21%) of the tested cheese samples did not correspond to the microbiological criteria according to the applicable regulations.